2020
DOI: 10.5812/aapm.99094
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phenylephrine Infusion on Maternal Hemodynamic Changes During Spinal Anesthesia for Cesarean Delivery

Abstract: Background: Spinal anesthesia is used as a common anesthetic technique in many routine and outpatient surgeries. Objectives: The aim of this study was to determine the effect of phenylephrine on maternal hemodynamic changes during spinal anesthesia for cesarean delivery. Methods: This double-blind randomized controlled trial was conducted on 116 pregnant women candidate for the elective cesarean section through spinal anesthesia in the Shahid Akbarabadi Hospital, Tehran in 2019. The eligible women were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Moreover, a spinal block technique can take a shorter time than an epidural block (3). Some studies mentioned that spinal analgesia not only can be applied more easily but also is faster, less expensive, and more effective than epidural analgesia (4)(5)(6)(7)(8)(9)(10)(11). Administration of opioid drugs in neuraxial blocks, which do not affect the sympathetic activity, along with local anesthetics, is a common technique to avoid negative consequences such as hypotension in these techniques (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a spinal block technique can take a shorter time than an epidural block (3). Some studies mentioned that spinal analgesia not only can be applied more easily but also is faster, less expensive, and more effective than epidural analgesia (4)(5)(6)(7)(8)(9)(10)(11). Administration of opioid drugs in neuraxial blocks, which do not affect the sympathetic activity, along with local anesthetics, is a common technique to avoid negative consequences such as hypotension in these techniques (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…This issue was more prominent when another author added glucose to the crystalloid solution (15). In contrast, another study has revealed that infusion of phenylephrine to prevent overt either hypotension or bradycardia was associated with better symptom (nausea and vomiting) control and also resulted in favorable neonatal blood gas outcomes (16). Although we used crystalloid for all participants, the latter finding showed that the effect of other parameters should be kept in mind.…”
Section: Discussionmentioning
confidence: 91%
“…The study results showed that phenylephrine compared to saline had no effect on patients' hypotension and tachycardia, but had a significant effect on patients' heart rate [20], which is consistent with the results of this study. In a study by Shafeinia et al on 116 patients in the phenylephrine and normal saline control groups, it was shown that phenylephrine reduced some of the complications of pregnant women undergoing cesarean section, such as hypotension (systolic and diastolic), arterial hypertension, nausea and vomiting [17]. Also in a study by Nikooseresht et al, 120 patients undergoing cesarean section were divided into 3 groups: Therapeutic Bolus, Prophylactic Bolus and Prophylactic Infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic information checklist including information on age, gender, height, weight, gestational age, blood pressure (systolic and diastolic), heart rate, and Apgar score (first and fifth minutes) was used. The patients' nausea was also divided into 4 categories without nausea (score zero), low nausea (score one), high nausea (score 2) and vomiting [17].…”
Section: Data Gatheringmentioning
confidence: 99%